2015
DOI: 10.11005/jbm.2015.22.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Fracture in a Young Male Patient Leading to the Diagnosis of Wilson's Disease: A Case Report

Abstract: Wilson's disease is a rare genetic disorder that has abnormal copper metabolism. Although the disease's main problems are found in liver and brain, some studies revealed manifestation of various musculoskeletal problems in the patients. In this report, we encountered a young patient who had fracture in the forearm bone. Initially, exception to a previous history of fracture from a motorcycle accident, the patient did not have any medical or drug use history, and laboratory work-ups were insignificant. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…A review of Indian patients reported refractory rickets and renal tubular diseases in approximately one-third of the cases of 25 patients with WD (47,48).…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…A review of Indian patients reported refractory rickets and renal tubular diseases in approximately one-third of the cases of 25 patients with WD (47,48).…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…R heu matoid problems are a not her classic early manifestation of WD characterized by joint or osseous pain as well as demineralisation leading to unusual bone fractures (7,(83)(84)(85). Misra et al reported a 30-year-old patient with slowly progressive pain in the small and large joints for 14 years (85).…”
Section: Other Rare Extra-hepatic Presentations At Diagnosismentioning
confidence: 99%
“…However, they might be a result of a complex pathophysiological mechanism of this disease, as it is known that there is a connection between copper metabolism, copper plasma levels and bone health 27 . In addition, bone fractures have also been described in Menkes and Wilson disease 28,29 …”
Section: Discussionmentioning
confidence: 99%